The role of cross-sectional geometry of high-head gated conduit in oxygen transfer efficiency - Baylar, Ahmet; Ozkan, Fahri; Yildirim, Ceren Beyza; Aydin, Alp Bugra; Tuna, Muhammed Cihat; Ozturk, Mualla (Wiley, 2022)
The concentration of dissolved oxygen is an important indicator of water quality because aquatic life lives on the dissolved oxygen in the water. This can be achieved by using hydraulic structures because of substantial air bubble entrainment at these structures. Closed conduit aeration is a particular instance of this. In the present study, experiments were carried out to investigate the role of cross-sectional geometry of high-head gated conduit in oxygen transfer efficiency. In the first part of this study, the role of cross-sectional geometry of high-head gated conduit in air-demand ratio was investigated. In the second part, the role of cross-sectional geometry of high-head gated conduit in oxygen transfer efficiency was investigated. Results pointed that the cross-sectional geometry of the high-head gated conduit had an important effect on the air-demand ratio and the oxygen transfer efficiency. Moreover, a design formula was obtained for the conduit having the highest oxygen transfer efficiency relating the oxygen transfer efficiency to air-demand ratio, Froude number, gate opening, conduit length and gate opening ratio. There was good agreement between the measured and the predicted values. The obtained results will be useful in future modelling processes and aid the practicing engineer in predicting oxygen transfer efficiency of high-head gated conduits.
Keywords: air-demand ratio; high-head gated conduit; oxygen transfer efficiency